2001
DOI: 10.1002/aoc.195
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic in the prepared edible brown alga hijiki, Hizikia fusiforme

Abstract: To reduce the arsenic content of the leaves and branches of an edible brown alga, hijiki Hizikia fusiforme, the Japanese traditional washing and soaking process before cooking was shown to be effective: about 32 to 60% of the arsenic was removed from the alga at room temperature. Increasing the amount of water in which the hijiki was soaked did not affect arsenic removal. On the other hand, arsenic content decreased linearly as the temperature used to wash and soak hijiki increased from 0 to 60°C. In the washe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…The losses of arsenic were caused by solubilization in the cooking water. Hanaoka et al 8 have shown that treatments of washing and soaking with water applied before cooking reduce the t-As content of H. fusiforme in a range from 32% to 60%, the reduction being due mainly to loss of i-As. In our work, the results obtained after analysis of batch A, i.e.…”
Section: The T-as and I-as Contents In Raw And Cooked H Fusiformementioning
confidence: 99%
See 1 more Smart Citation
“…The losses of arsenic were caused by solubilization in the cooking water. Hanaoka et al 8 have shown that treatments of washing and soaking with water applied before cooking reduce the t-As content of H. fusiforme in a range from 32% to 60%, the reduction being due mainly to loss of i-As. In our work, the results obtained after analysis of batch A, i.e.…”
Section: The T-as and I-as Contents In Raw And Cooked H Fusiformementioning
confidence: 99%
“…For edible seaweed the situation might well be different, as high contents of i-As have been quantified in species such as Hizikia fusiforme, 4 -7 attaining 135 mg kg −1 dry weight (DW), 91% of the total arsenic (tAs). 8 These high contents do not seem to be attributable to growth of the seaweed in an environment contaminated by arsenic, but rather to its natural tendency to accumulate iAs. We are not aware of any studies that evaluate dietary exposure to i-As in seaweed, but an estimation performed by Almela et al 6 on the basis of an analysis of various seaweeds showed that the risk of exceeding the PTWI value is a reality with a consumption of 3 g day −1 of H. fusiforme.…”
Section: Introductionmentioning
confidence: 97%
“…6,7) Previous studies on arsenic in seaweed have shown that the majority of arsenic can easily be extracted by water or water/methanol extraction. 34) Our values of the total-As obtained by water extraction using ultrasonication are consistent with the values already reported.…”
Section: Discussionmentioning
confidence: 99%
“…5) The iAs concentration in hijiki depends on the producing district and manufacturing method. 6,7) Five oxoarsenosugars (oxo-AsSugs) have been detected in hijiki as well as other seaweeds. [8][9][10] In humans, oxo-AsSug is metabolized and excreted into urine as dimethylarsinic acid (DMA) and several oxoor thio-dimethylarsenic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…4,5,10 -14 Total arsenic concentrations in these marine organisms are reported *Correspondence to: Mio Takeuchi, Institute for Geo-Resources and Environment, National Institute of Advanced Industrial Science and Technology (AIST), 16-1 Onogawa, Tsukuba, Ibaraki 305-8569, Japan. E-mail: takeuchi-mio@aist.go.jp to be <231.0 mg kg −1 dry weight for macroalgae 15 and <340.1 mg kg −1 wet weight for marine animals. 1 The concentrations of these organoarsenicals in marine organisms are well known.…”
Section: Introductionmentioning
confidence: 99%